2020
DOI: 10.1590/1984-0462/2020/38/2018242
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Cultural Adaptation of the Mediterranean Diet Quality Index in Children and Adolescents

Abstract: Objective: To translate and culturally adapt the Mediterranean Diet Quality Index in Children and Adolescent (KIDMED) for the Brazilian population. Methods: The processes of translation and cultural adaptation followed internationally standardized methodological norms. We used the intraclass correlation coefficient and the Bland-Altman dispersion analysis to assess the reproducibility and calculated the internal consistency with Cronbach’s alpha coefficient. Results: A total of 102 children and adolescents p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Given that it is a simple instrument to use, many countries in the Mediterranean area such as Croatia ( 11 ), Greece ( 12 14 ), Hungary ( 10 ), Israel ( 15 ), Italy ( 16 18 ), Lebanon ( 19 ), Lithuania ( 11 ), Portugal ( 20 – 22 ), Serbia ( 11 ), Spain ( 23 – 26 ), and Turkey ( 27 29 ) have used this instrument to measure the adherence to the Mediterranean diet in children and young people. Furthermore, other countries which, due to their geographical position and gastronomic culture, have access to foods typical of the Mediterranean pattern such as Brazil ( 30 ), Chile ( 31 ), Colombia ( 32 ), Cyprus ( 33 ), Estonia ( 34 , 35 ), Finland ( 36 ), and the United States ( 37 39 ) have also used the questionnaire.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that it is a simple instrument to use, many countries in the Mediterranean area such as Croatia ( 11 ), Greece ( 12 14 ), Hungary ( 10 ), Israel ( 15 ), Italy ( 16 18 ), Lebanon ( 19 ), Lithuania ( 11 ), Portugal ( 20 – 22 ), Serbia ( 11 ), Spain ( 23 – 26 ), and Turkey ( 27 29 ) have used this instrument to measure the adherence to the Mediterranean diet in children and young people. Furthermore, other countries which, due to their geographical position and gastronomic culture, have access to foods typical of the Mediterranean pattern such as Brazil ( 30 ), Chile ( 31 ), Colombia ( 32 ), Cyprus ( 33 ), Estonia ( 34 , 35 ), Finland ( 36 ), and the United States ( 37 39 ) have also used the questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by Aparicio-Ugarriza et al ( 10 ) analyses the psychometric properties of the KIDMED, but they only consider the index score. Therefore, to our knowledge, there are only three studies that have examined the psychometric properties of the KIDMED in children and adolescents in two countries: Colombia ( 32 ), Brazil ( 30 ), and Portugal ( 21 ). Specifically, the study conducted by Carrillo and Ramírez-Vélez ( 32 ) showed adequate overall internal consistency of the questionnaire, except for Items 1, and 2.…”
Section: Introductionmentioning
confidence: 99%